Experimental study on freeze-thaw damage characteristics and mechanical properties of fractured rock mass of surface mine slope in cold region - Sen TIAN; Ying ZHAO; Hu SI; Chun ZHU; Quangui LI (Meitan xuebao)
There are numerous large-scale rock slopes in the surface mines of China, which are easily affected by multiple factors such as complex geological topography and natural, engineering disturbances, thereby resulting in frequent landslide disasters. Especially in northwest China, the landslides in surface mines occur frequently due to the complicated topographical and geological structures, harsh climate and environment, as well as long-term engineering disturbance, which seriously threaten miner’s life and property safety. From the perspective of macro-micro damage evolution of characteristic slope rock masses, this study conducted the freeze-thaw test, the frost heave force evolution test, and the uniaxial compression test of fractured rock masses in the potential landslide area, based on the actual engineering geological and environmental characteristics of high-steep rock slope at an surface mine in Xinjiang province. Where multi-faceted research approaches including engineering field investigation, theoretical analysis and laboratory experimental research were adopted, and the theories and methods of rock mechanics and soil mechanics were integrated. Through these tests, the mass loss, wave velocity attenuation and frost heave force evolution characteristics of fractured rock masses with different inclinations (0°, 25°, 50°, 75°) were analyzed under different freeze-thaw cycles, and the strength and aging characteristics of fractured rock masses under different load conditions, along with the evolution of their mechanical properties under different freeze-thaw cycles were revealed. On this basis, combined with the synchronous acoustic emission test, the final rock fracture mode, the morphology and macro-micro propagation mechanisms of cracks during the rock deformation and failure process were expounded. The results show that under the action of freeze-thaw cycles (0, 10, 20, 30 times), the saturation mass of rock masses increased first and then decreased, while the P-wave velocity showed a decelerated decay. The evolution of frost heave force could be divided into five stages: the incubation stage, the heaving stage, the stabilization stage, the secondary heaving stage and the melting stage. Moreover, the generation of frost heave force, the time required to reach peak and the peak values were all positively correlated with the fracture inclination. The peak values of frost heave forces of rock samples with crack inclinations (0°, 25°, 50°, 75°) are 3.68, 3.88, 4.04, 4.13 MPa, respectively. The frost heave effect resulted in a decreased strength of rock masses due to the repeated tensioning action, which was a major cause of slope instability in this cold region. The stress-strain relationship of rock masses under uniaxial compression and the trend of crack volume strain were roughly the same, which could be divided into five typical stages: the microfracture closure stage, the elastic deformation stage, the yield stage, the crack acceleration stage and the post-peak stage. The compressive strength and elastic modulus of rock masses decreased linearly with the increase of freeze-thaw cycles, while increased linearly with the increase of fracture inclination. According to the final fracture morphology of rock samples and the Gaussian mixture model-based classification of microcracks, the tensile fracture was the predominant microfracture mode of rock samples (up to 54.2%), followed by the mixed mode (up to 42.3%). With the increase of freeze-thaw cycles (20–30 times), the proportion of mixed-mode microcracks increased and that of shear cracks decreased. Moreover, the macroscopic failure mode was the mixed tensile–shear failure.